2018
DOI: 10.1002/cphc.201701352
|View full text |Cite
|
Sign up to set email alerts
|

One‐Pot Soft‐Template Synthesis of Nanostructured Copper‐Supported Mesoporous Carbon FDU‐15 Electrocatalysts for Efficient CO2 Reduction

Abstract: Copper-supported mesoporous carbon nanocatalysts (Cu/FDU-15) were synthesized using an easy and convenient one-pot soft-template method for low-overvoltage CO electroreduction. TEM imaging revealed the presence of large Cu nanoparticles (diameter 140 nm) with Cu O nanoparticles (16 nm) as an additional phase. From the electron tomography observations, we found that the copper particles were placed inside and on the exterior surface of the porous FDU-15 support, providing an accessible surface for electrocataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 53 publications
3
11
0
Order By: Relevance
“…The low The XRD patterns of the Cu/MC sample in Fig. 3 exhibit characteristic diffractogram peaks of the metallic phase of Cu(0), which corresponds to 2θ values of 43.47°, 50.63°, and 74.19° and of Cu(I), which corresponds to 2θ value of 36.62° [13,25,[29][30]. This result indicates that two Cu species existed in Cu/MC due to the reduction of copper(II) salt with hydrogen gas during calcination.…”
Section: Characterization Of Cu/mc Catalystmentioning
confidence: 99%
See 1 more Smart Citation
“…The low The XRD patterns of the Cu/MC sample in Fig. 3 exhibit characteristic diffractogram peaks of the metallic phase of Cu(0), which corresponds to 2θ values of 43.47°, 50.63°, and 74.19° and of Cu(I), which corresponds to 2θ value of 36.62° [13,25,[29][30]. This result indicates that two Cu species existed in Cu/MC due to the reduction of copper(II) salt with hydrogen gas during calcination.…”
Section: Characterization Of Cu/mc Catalystmentioning
confidence: 99%
“…It can assist the loading process of active catalyst species, facilitate good reactant transport, and expand the temperature range in reaction applications. It is known that mesoporous carbon can be impregnated well with various types of metals for multiple applications such as Ag [19][20], Pd [20], Ni [21][22], Co [23], Ru [24], and Cu [25]. In addition, mesoporous carbon is also a potential material to be used as a CO2 adsorbent [26][27].…”
Section: ■ Introductionmentioning
confidence: 99%
“…Gas Chromatography (GC) is most commonly used to analyze a wide range of permanent gas/organics/hydrocarbons with a reasonable analysis time (3-60 min/sample). [11][12][13] Other analytical instruments including High Performance Liquid Chromatography (HPLC), 14,15 nuclear magnetic resonance (NMR) spectroscopy, 11 ion chromatography, 16 and ultraviolet-visible (UV-Vis) spectroscopy 17 were reported for liquid phase analysis with sample throughput rates commonly reported at <10 samples/day. Kuhl et al 3 recently developed a reaction vessel based on large planar electrodes with small electrolyte volume to accelerate concentration of products and enable detailed analytical chemistry information for the CO 2 reduction reaction (CO 2 RR).…”
Section: Introductionmentioning
confidence: 99%
“…So, this has leading studies on electrochemical production of methane and ethylene on copper-based electrodes. Recently reported studies have also been demonstrated that threedimensional porous electrode materials 18,26 that favour easy diffusion of electrolyte, fast kinetics of electrochemical reactions, and steps of readsorption of reaction intermediates are highly desirable for constructing high performance electrode materials in electrocatalysis. In particular, the influence of the interconnected porous channels as transport paths on electrolyte transportation and ion diffusion have been demonstrated [27][28][29] .…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis was based on the one pot soft-template process which has shown the lead easily to accessible nanostructured metal-based phase well dispersed in a mesoporous carbon structure. 26 We further discuss the role of the electrode potential on product selectivity of short-chain hydrocarbons determined by on-line differential electrochemical mass spectroscopy and chromatographic analysis.…”
Section: Introductionmentioning
confidence: 99%